Penyajian Musik Dalam Acara Pernikahan Nasional oleh Shine Music di Kota Medan - Sheren Regina Stefani; Ance Juliet Panggabean; Junita Batubara (SENDRATASIK UNP, 2022)
This study aims to describe the presentation of music in the National wedding ceremony by Shine Music in Medan City. This type of research is descriptive qualitative. Data collection techniques were carried out by means of literature study, observation, interviews and documentation. The results of this study indicate that Shine Music has the advantage that it is able to develop in the industrial world in the city of Medan, especially in filling international wedding events in Medan. Shine Music has band and orchestra formats, but the term "orchestra" in the Shine Music format is not the same as the orchestral format used in academia. The term "orchestra" in Shine Music is used as a branding/promotion in the music industry business world in Medan to popularize the name Shine Music and has many fans. The author examines the Shine Music management system which is conceptualized and carries out its duties professionally. This is the advantage of Shine Music so that it can develop as a music organizer in the city of Medan.